Transiçao curricular da Cidade de Sao Paulo : impactos da participaçao na elaboraçao do Currícula nas concepçoes dos profesores de Ensino Fundamental I no trabalho com problemas em suas aulas de matemática - Lopes Robles, Laís (2021)
Since 2017, the "Secretaria Municipal de Sao Paulo" has been taking actions to plan the production and implementation of a new curriculum, called "Currículo da Cidade", adapting its materials to the provisions of the normative document Base Nacional Comum Curricular" (BNCC), approved also in 2017. Bearing in mind that the "Currículo da Cidade" was a collaboratively elaborated document, the present work aims to analyze the impacts of participation in the elaboration of the curriculum at work with problems in elementary school math classes. The research, based on bibliographic studies, documentary analysis and interviews, raised comparative data in order to analyze how the participation in the curriculum development actions contributed to a change in the teachers' conception when reporting on the work done. The analysis of comparative data, based on concepts from the perspective of Didactics of Mathematics, pointed out the relevance of the participation of teachers in the elaboration of the curriculum, as well as the space for reflection and training of teachers on mathematical practice, the curriculum and work with problems.